2014
DOI: 10.1186/2193-1801-3-109
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and intended usage preferences for six HIV testing options among internet-using men who have sex with men

Abstract: BackgroundMen who have sex with men (MSM) continue to be disproportionately impacted by the Human Immunodeficiency Virus (HIV) epidemic in the United States (US). Testing for HIV is the cornerstone of comprehensive prevention efforts and the gateway to early engagement of infected individuals in medical care. We sought to determine attitudes towards six different HIV testing modalities presented collectively to internet-using MSM and identify which options rank higher than others in terms of intended usage pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 46 publications
7
55
1
Order By: Relevance
“…The majority of the studies included communities at high risk of HIV infection. Ten studies included MSM, 21,[47][48][49][50][51][52][53]56,57 three included people who inject drugs (PWID) 46,47,50 and three included non-specified individuals or clinic populations who practised high-risk activities. 21,54,55 Only two studies focused on heterosexual populations who practised high-risk activities (both studies were based in the USA); 47,50 all of the UK studies included only MSM.…”
Section: Results Of the Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies included communities at high risk of HIV infection. Ten studies included MSM, 21,[47][48][49][50][51][52][53]56,57 three included people who inject drugs (PWID) 46,47,50 and three included non-specified individuals or clinic populations who practised high-risk activities. 21,54,55 Only two studies focused on heterosexual populations who practised high-risk activities (both studies were based in the USA); 47,50 all of the UK studies included only MSM.…”
Section: Results Of the Systematic Literature Reviewmentioning
confidence: 99%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk The majority of the studies evaluated a dried blood spot SSK (n = 8), 21,46,47,50,[53][54][55]57 whereas five studies assessed an oral fluid test 21,48,49,51,55 (two studies assessed both types of sampling 21,55 and another two did not specify the type of test 52,56 ).…”
Section: Systematic Policy and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…28,30 An important first step in the development of a combined package of HIV-prevention tools for MSM in South Africa is to determine which prevention tools MSM know, are willing to use, and understand as necessary to protect against HIV. 31 This article presents qualitative data obtained from focus groups of MSM and health service providers recruited in Cape Town and Port Elizabeth, to examine perceptions of the HIV-prevention needs of MSM. The focus is on comparing the perceptions of MSM (the clients) and service providers in order to inform the development of a combined package of HIV prevention tools tailored to the specific needs of MSM and to highlight the public health messaging and training strategies that are needed to successfully implement the package.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent US study in MSM populations in which options to test were offered to study participants reported that home self-tests and testing in physicians' offices were most preferred by them. 32 These studies indicate that because patients prefer home tests, therefore perhaps, improving testing frequency with provision of many self-tests might help offset some of the limitations of these tests in picking up acute HIV infection (at 90 days vs. 30 days or less). Repeat self-testing could be emphasized and highlighted for some sub-populations or individuals with high-risk profiles.…”
Section: Global Evidence On Self-testingmentioning
confidence: 99%